Capsaicinoids, antioxidant activity, and volatile compounds in olive oil flavored with dried chili pepper (Capsicum annuum). Issue 12 (8th November 2013) - Caporaso, Nicola; Paduano, Antonello; Nicoletti, Giovanna; Sacchi, Raffaele
<x xml:space="preserve">Abstract</x> Spices and herbs are traditionally added to olive oil in Mediterranean gastronomy to enhance its aroma and taste. This paper aims to characterize olive oil aromatized by addition of dried chili pepper (Capsicum annum) (DCP) at different concentrations (10% and 20% by weight) up to 30 days of infusion. Capsaicinoids quantification by HPLC‐DAD, volatile compounds analysis by SPME‐GC–MS and antioxidant activity by ABTS method were performed on chili pepper flavored olive oil (CPOO) in comparison to whole olive oil. At day 7 of infusion, the maximum capsaicinoids content was reached for both the concentrations used and no significant increase was observed for longer infusion times. The volatile headspace composition of CPOOs was influenced by the concentration of DCP added. The addition of DCP caused a significant increase in hexanal, related to oxidation processes. 2‐Methylbutanal, 3‐methylbutanal and 6‐methyl‐5‐hepten‐2‐one were also detected in CPOO and derived from chili as degradation products of the drying process. DCP infusion significantly enriched olive oil with antioxidant compounds and also modified its volatile profile. Capsaicinoids and aroma compounds were rapidly released within the first week of chili infusion in CPOOs, thus suggesting reducing infusion time by optimizing DCP concentration in order to improve CPOO quality and shelf life. Practical applications: The present research is relevant at industrial level for the optimization of olive oil flavoring and the aromatization process. In particular, we defined that the common infusion times of chili, used at industry production for flavoring olive oil, is longer than needed and we suggest reducing infusion time thus also avoiding problems of free acidity and PV increase. Also, we highlighted the importance of quality control for the chili pepper drying procedure and storage time before use, due to the possible formation of off‐flavors in the final product. Moreover, in the present paper a quantification method of the pungent molecules capsaicin and dihydrocapsaicin directly from flavored olive oil was applied. This method could be applied instead of empirical techniques such as Scoville units, for the definition and standardization of the capsaicinoids content in flavored oils and their pungency levels.